Implementasi UU Nomor 44 Tahun 2009 dan Implikasinya pada Sistem Manajemen Rumah Sakit: Review Sistematis - Mujtahidah; Nurul Fajriah Istiqamah (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2025)
Law Number 44 of 2009 concerning Hospitals (Law 44/2009) provides a legal framework that emphasizes improving the quality of services, protecting patients' rights, and accreditation of health institutions as an instrument of accountability. However, the implementation of this regulation still faces challenges, especially in the consistency of fulfilling patient rights, legal accountability, equitable distribution of service quality, and the use of the Hospital Management Information System (SIMRS). This study aims to systematically review the literature related to the implementation of Law 44/2009 and its contribution to hospital governance, focusing on accreditation, service quality, patient rights, and the implementation of SIMRS. The method used is a narrative literature review of seven published articles for the 2020-2025 period that are relevant to the topic. The analysis was carried out thematically to map patterns, challenges, and opportunities in the implementation of regulations. The results of the study show that although Law 44/2009 has pushed hospitals towards better governance, the realization in the field has not been evenly distributed. Patient rights and legal accountability still vary, service quality improved but limited to specific facilities, while SIMRS proved effective in supporting efficiency, transparency, medical record management, and disaster preparedness, despite infrastructure and human resource capacity. It was concluded that the successful implementation of Law 44/2009 does not only depend on the regulatory framework, but also on technology integration, strengthening human resources, and patient safety culture to ensure sustainable service quality